2018
DOI: 10.1590/0102-7786333007
|View full text |Cite
|
Sign up to set email alerts
|

Interannual and Intraseasonal Variations of the Onset and Demise of the Pre-Wet Season and the Wet Season in the Northern Northeast Brazil

Abstract: The Northern Northeast Brazil (NNB) has two rainy periods, namely Pre-Wet Season (PWS) and Wet Season (WES), which are usually treated as one system. The precipitation pattern on NNB is influenced by sea surface temperature (SST) anomalies in the Atlantic and Pacific Ocean on interannual timescales particularly by the Interhemispheric Gradient of SST anomalies (IGS) and El Niño Southern Oscillation (ENSO). On intraseasonal time scales, the MJO is especially important. This study investigates the variability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
(45 reference statements)
0
10
0
1
Order By: Relevance
“…When the position of this system is shifted abnormally south a few months before the onset of the wet season in the northern NEB, the meridional TSA mode increases moisture transport and rainfall during the wet months (Hounsou‐Gbo et al ., 2015). At the interannual and intraseasonal scales, the influence is associated with the occurrence of El Niño episodes and the Madden‐Julian Oscillation (MJO), respectively (Vasconcelos Junior et al ., 2018). At the intraseasonal time scale, the Southern Semiarid region is influenced by the interaction between the South Atlantic Convergence Zone (SACZ), the Bolivian High (BH) and UTCV.…”
Section: Resultsmentioning
confidence: 99%
“…When the position of this system is shifted abnormally south a few months before the onset of the wet season in the northern NEB, the meridional TSA mode increases moisture transport and rainfall during the wet months (Hounsou‐Gbo et al ., 2015). At the interannual and intraseasonal scales, the influence is associated with the occurrence of El Niño episodes and the Madden‐Julian Oscillation (MJO), respectively (Vasconcelos Junior et al ., 2018). At the intraseasonal time scale, the Southern Semiarid region is influenced by the interaction between the South Atlantic Convergence Zone (SACZ), the Bolivian High (BH) and UTCV.…”
Section: Resultsmentioning
confidence: 99%
“…Vasconcelos Jr et al (Vasconcelos Junior et al, 2018) showed that the precipitation variability over the NNB varies considerably during the PWS (NDJ) and WES F I G U R E 2 Composites of filtered OLR anomalies during MJO life cycle. Light (dark) grey depicts positive (negative) anomalies.…”
Section: Resultsmentioning
confidence: 99%
“…Vasconcelos Jr et al (Vasconcelos Junior et al ., 2018) showed that the precipitation variability over the NNB varies considerably during the PWS (NDJ) and WES (FMAM) periods. Figure 5 shows monthly proportions of CEPE occurrences for the two types of thresholds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations